A New Ichnospecies of Gyrolithes from the Austin Chalk, Upper Cretaceous, Texas, USA. Issue 1 (2nd January 2019) - Morgan, Ryan F.
ABSTRACT: Gyrolithes, a helical marine trace fossil, occurs in beds of the Austin Chalk near Waco, McLennan County, Texas. The new ichnospecies Gyrolithes texanus is characterized by unique morphology and wall construction. This discovery expands the current geographic and environmental range of Gyrolithes, extending this ichnogenus into the chalk-dominated beds of the Cretaceous of Texas. Irregular bedding features from the Gyrolithes locality indicate this section of the Austin Chalk was deposited within a storm-dominated depositional regime, interspersed with periods of quiescence which allow for firm ground formation and colonization by the trace maker. Occurrences of Gyrolithes have been associated by previous publications with marginal marine settings but not associated with storm deposits; therefore, this discovery constitutes an expansion of associated environment for this ichnogenus.